Banning the Bing: Why Extreme Solitary Confinement Is Cruel and Far Too Usual Punishment - Bennion, Elizabeth (2015)
The United States engages in extreme practices of solitary confinement that maximize isolation and sensory deprivation of prisoners. The length is often indefinite and can stretch for weeks, months, years, or decades. Under these conditions, both healthy prisoners and those with preexisting mental-health issues often severely deteriorate both mentally and physically. New science and data provide increased insight into why and how human beings (and other social animals) deteriorate and suffer in such environments. The science establishes that meaningful social contacts and some level of opportunity for sensory enrichment are minimum human necessities. When those necessities are denied, the high risks of serious harm apply to all prisoners, no matter how seemingly resilient beforehand. Given these facts, this Article argues that solitary confinement, as commonly practiced in the United States, is cruel and unusual punishment—whether analyzed under current Supreme Court standards or an improved framework. Furthermore, recently released data on states implementing reforms shows that extreme solitary confinement tactics are counterproductive to numerous policy interests, including public safety, institutional safety, prisoner welfare, and cost efficiency. Both the scientific and the policy data suggest possible avenues for effective reform